Asset Recovery in the Perspective of the United Nations Convention Against Corruption (UNCAC) and Its Implementation in Indonesia - Ronald Hasudungan Sianturi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes asset recovery arrangements from the perspective of the United Nations Convention Against Corruption (UNCAC) and its implementation in Indonesia. Using normative legal research methods with legislative, conceptual, and comparative approaches, this study finds that there is still a significant normative gap between the provisions of UNCAC Chapter V and the Indonesian domestic legal framework, especially in terms of the adoption of the non-conviction based forfeiture mechanism. Institutional obstacles in the form of overlapping authority, weak coordination, and limited human resource capacity also hinder the effectiveness of asset recovery. The Asset Forfeiture Bill, which carries an in rem and asset sharing mechanism, is an important breakthrough, but its success requires strengthening institutional capacity, harmonizing regulations, and protecting human rights for well-intentioned third parties. This study recommends accelerating the ratification of the Asset Forfeiture Bill, strengthening coordination between law enforcement agencies, and improving the competence of officials in tracking and recovering assets across countries.